ANALISIS KERAGAMAN DAN KEKERABATAN KACANG TUNGGAK (Vigna unguiculata L) GENERASI M2 - Yukarie Ayu Wulandari; Sobir Sobir; Syarifah Iis Aisyah (Jurnal AGROSAINS dan TEKNOLOGI, 2020)
Cowpea (V. unguiculata L) has great potential as a nutritious food as a substitute for soybeans because it contains sufficient protein and low fat content. The diversity of cowpea is low so that need to increase diversity through the mutation induction of gamma ray irradiation. The study was carried out in the experimental garden of Pasir Kuda PKHT of IPB in February - May 2018 using a design of augmented in the Complete Group Design in a Randomized. The study was carried out using 90 putative mutant genotypes of M2 generation as the test genotype and KM4 genotype as a comparison which was repeated 10 times. The results showed that the M2 generation putative mutants showed diversity in the qualitative and quantitative characters of cowpea. High genetic diversity is shown in the character of plant height, harvest period, number of seeds / pods and weight of cowpea seeds / plants and high broad mean heritability values obtained on the character of stem length, flowering age, number of seeds / pods and weight of beans / plant nuts arrears. The result of kinship analysis showed thirteen different putative mutant genotypes with KM4 genotypes, namely T6599P, T8028P, T7525P, T7551P, T7520P, T6574P, T6533P, T7058P, T6577P, T6591P, T7062P, T7069P and T6561.